2014
DOI: 10.1142/s1793042114500730
|View full text |Cite
|
Sign up to set email alerts
|

A generalized family of multidimensional continued fractions: TRIP Maps

Abstract: Most well-known multidimensional continued fractions, including the Mönkemeyer map and the triangle map, are generated by repeatedly subdividing triangles. This paper constructs a family of multidimensional continued fractions by permuting the vertices of these triangles before and after each subdivision. We obtain an even larger class of multidimensional continued fractions by composing the maps in the family. These include the algorithms of Brun, Parry-Daniels and Güting. We give criteria for when multidimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…The proof is almost exactly the same as the proof in Theorem 6.2 in [6]. That proof shows that there is an invertible 3 × 3 matrix A with integer entries so that…”
Section: Barycentric Triangle Partition Mapsmentioning
confidence: 68%
See 4 more Smart Citations
“…The proof is almost exactly the same as the proof in Theorem 6.2 in [6]. That proof shows that there is an invertible 3 × 3 matrix A with integer entries so that…”
Section: Barycentric Triangle Partition Mapsmentioning
confidence: 68%
“…Thus, Panti turns to the ndimensional generalizations of these maps, known as the Mönkemeyer map (M) and the tent map (T ) to find his generalization of ?(x). (At this point the reader should note that Dasratha et al showed in [6] that the Mönkemeyer map in the 2-dimensional case corresponds to the TRIP map T (e,132,23) , a fact that we will later be exploiting.) Defining △ as the n-dimensional simplex that reduces to our familiar triangle in 2-dimensions, he presents the following…”
Section: Panti's Workmentioning
confidence: 84%
See 3 more Smart Citations